Simulation of Direct Laser Writing of YBa2Cu3O7-x/SrTiO3/MgO Structure for Fabrication of Josephson Junction - R. A. Sani; E. H. Sujiono; T. Winata; M. Barmawi (Institut Teknologi Bandung, 2001)
Fabrication of Josephson junction devices could be easily carried out using direct laser writing techniques. Thin film superconductor can be etched by melting it using a focused laser beam. While the laser beam is fixed, the etching pattern can be generated by moving the thin film on an X-Y table, which could be controlled by a computer. The melting radius is determined by the laser power density and the scanning-speed. The optimized scanning speed for fixed power density is predicted by solving the heat equation using finite element method. We consider a structure consisting of MgO substrate, a bufferlayer SrTiO3 and the superconducting YBCO film. The simulation is carried out for laser power of 1 to 5 watt at the wavelength of 514 nm.